Intervention in Developmental Language Disorder (DLD). A systematic review (2000-2020) - Bahamonde Godoy, Claudio; Serrat Sellabona, Elisabet; Vilà Suñè, Montserrat (Revista de Investigación en Logopedia, 2021)
This paper presents the results of a systematic review of the scientific production about the DLD intervention (formerly know as Specific Language Impairment, SLI) from the period 2000-2020. Thirty- one publications are located in the DIALNET and EBSCO databases, which meet the following selection criteria: publication year, language (English and Spanish), peer-review and interventions in population with DLD or SLI. Are analyzed among others, the following dimensions: intervention objectives, strategies, collaboration, results and declared limitations. The main findings refer to the irruption of the concept of Developmental Language Disorder (DLD) in recent years, preference for experimental and quasi-experimental designs, positive results that coexist with modest gains in most of the studies analyzed. The main limitations are the absence of a control group and differentiation of effects. The conclusions point to the for more interventions based on an interactive-collaborative approach, expand the coverage of objectives towards the learning and cognitive needs derived from DLD and consider within-subject designs, with observation of medium and long-term effects that includes youth and adults.
Keywords: DLD; SLI; Collaborative intervention; Intervention